2006
DOI: 10.1016/j.jhealeco.2005.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Does falling smoking lead to rising obesity?

Abstract: The strong negative correlation over time between smoking rates and obesity have led some to suggest that reduced smoking is increasing weight gain in the U.S. This conclusion is supported by findnigs of Chou et al. (2004), who conclude that higher cigarette prices lead to increased body weight. We investigate this issue and find no evidence that reduced smoking leads to weight gain. Using the cigarette tax rather than the cigarette price and controlling for non-linear time effects, we find a negative effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
205
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(220 citation statements)
references
References 19 publications
12
205
2
1
Order By: Relevance
“…6 The study also showed that rising cigarette prices lead to an increase in body weight in the US [45]. As, however, the latter finding was contested by Gruber et al, who found the opposite effect using cigarette taxes rather than prices as a variable in their explanatory model [46], I did not factor cigarette taxes or prices into the equation. 7 The GSOEP does not indicate if the individual is pregnant in the respective time period or not.…”
Section: Resultsmentioning
confidence: 93%
“…6 The study also showed that rising cigarette prices lead to an increase in body weight in the US [45]. As, however, the latter finding was contested by Gruber et al, who found the opposite effect using cigarette taxes rather than prices as a variable in their explanatory model [46], I did not factor cigarette taxes or prices into the equation. 7 The GSOEP does not indicate if the individual is pregnant in the respective time period or not.…”
Section: Resultsmentioning
confidence: 93%
“…Courtemanche and Carden (2011) find that the proliferation of Walmart Supercenters has increased obesity, at least partially by lowering food prices. Chou et al (2004) and Baum (2009) find that higher cigarette prices have exacerbated obesity, although Gruber and Frakes's (2006) results show that higher cigarette taxes are negatively associated with obesity. In 1964, the U.S.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Recently, researchers have begun examining the effects of various socio-environmental changes, which may have affected net calories consumed, on the prevalence of obesity. For example, Baum (2007) examines changes in the racial and ethnic composition and age distribution; Lakdawalla and Philipson (2007) examine employment and physical activity at work; Cutler et al (2003), Chou et al (2004), Rashad and Grossman (2004), and Rashad et al (2006) examine the prevalence of restaurants and food prices; Chou et al (2004) and Gruber and Frakes (2006) examine cigarette prices and taxes; Gibson (2003), Chen et al (2005), Meyerhoefer and Pylypchuk (2008), and Baum (2011) examine food stamp receipt; and Ewing et al (2003), Eid et al (2008), and Zhao and Kaestner (2010) examine urban sprawl.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, smoking is associated with multiple chronic morbidities and elevated mortality risks. On the other hand, smoking is associated with lower BMI levels (Gruber and Frakes 2006;Keenan 2009;Nonnemaker et al 2009). Current physical activity and exercise have an inverse relationship with obesity (Lahti-Koski et al 2002).…”
Section: Individual Characteristics and Determinants Of Obesitymentioning
confidence: 99%